HUBUNGAN SOSIAL MAYORITAS ISLAM DENGAN MINORITAS AGAMA-AGAMA LAIN DI KOTA BANDA ACEH-INDONESIA - M. Nur, Hasan Basri; Packeer Mohamed, Syed Sultan Bee; Sham Rambely, Nor Azlah (JURNAL AL-IJTIMAIYYAH, 2021)
Abstract: Assumption from outsiders that Aceh is intolerant is truly disadvantage for Aceh which its majority is Muslims and implement Syria law. Looking on religious perspectives, the composition of Banda Aceh inhabitant is: Islam (97,96%), Buddha (1,13%), Christian (0,70%), Catholic (0,20), and Hindu (0,01). This research to find out how is social relationship between Muslim majority and other religious minority believers in Band Aceh. Social relationship framed in five aspects are religious, social, education, politic, economy and culture. This research used qualitative descriptive approach with observational data collection techniques, interview, and literature review. The finding of research showed that social relationship between believers in Banda Aceh runs in peace and interrelated. The existence of Muslims as great majority and Syria law implementation in Aceh has not been an obstacle in social activities of the minority. Muslims play roles as protectors and back shield for minority. Otherwise, the minorities are capable to adjust themselves and respect the existence of Islam showed on their attitudes, such as doing their formal prayer in designed places, their children wear polite dresses at schools even though not wearing hijab, participate in national and national election, close shops on Friday prayer, Muslim holidays, and mutual sending invitations to wedding party, involve in social work, and other activities.Keywords:  Social; Religion; Majority; Minority; Banda Aceh.Abstrak: Anggapan orang di luar bahwa Aceh tidak toleran sangat merugikan Aceh yang mayoritas penduduknya menganut agama Islam dan menerapkan Syariat Islam. Komposisi penduduk Banda Aceh berdasarkan agama adalah: Islam (97,96%), Buddha (1,13%), Kristen (0,70%), Katolik (0,20), dan Hindu (0,01). Penelitian ini hendak mengetahui bagaimana hubungan sosial antara mayoritas penduduk Islam dengan minoritas agama-agama lain di Banda Aceh. Hubungan sosial dibatasi dalam lima aspek, yaitu sosial agama, pendidikan, politik, ekonomi, dan budaya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data secara observasi, interview, dan kajian dokumen. Hasil penelitian menunjukkan bahwa hubungan sosial antar agama di Banda Aceh berlangsung damai dan saling mengisi. Keberadaan umat Islam sebagai mayoritas mutlak dan pemberlakuan Syariat Islam di Aceh tidak menjadi penghambat dalam aktivitas sosial umat minoritas. Umat Islam mampu memainkan peran sebagai pengayom dan pelindung bagi umat minoritas. Sebaliknya umat minoritas mampu menyesuaikan diri dan menghormati keberadaan Islam yang terlihat dari beberapa perilaku mereka, seperti beribadah di tempat-tempat resmi yang telah disediakan, anak-anak mereka mengenakan pakaian sopan di sekolah walau tak memakai jilbab, berpartisipasi dalam setiap momen Pemilu/Pilkada, menutup toko menjelang pelaksanaan shalat Jumat, hari raya Islam, serta saling mengundang/menghadiri pada pesta perkawinan, gotong royong dan lain-lain.Kata Kunci: Sosial; Agama; Mayoritas; Minoritas; Banda Aceh.